ANALISIS PROSES PEMBELAJARAN BENTUK BANGUN DATAR PADA SISWA TUNAGRAHITA MELALUI MEDIA GAMBAR BERWARNA - Maulana, Hikmat; Maula, Luthfi Hamdani; Uswatun, Din Azwar (JURNAL PENDIDIKAN DASAR PERKHASA: Jurnal Penelitian Pendidikan Dasar, 2025)
This study aims to describe the learning process, identify factors influencing success, and examine student and parent responses to the use of colored images in teaching geometric shapes. A qualitative approach with a case study method was employed. The subject was a sixth-grade student with intellectual disability at SDN Rancakadu, Sukabumi. The researcher acted as the primary instrument, supported by observation, interview, and documentation guidelines. Data were collected from the student and teachers. The results indicate that the learning process using colored images significantly facilitates the delivery and reception of information. Clear, simple, high-contrast, and brightly colored images effectively attract attention and enhance the student’s understanding of abstract geometric concepts. Color usage also strengthens memory retention. Success factors include the quality of image design, consistent, clear, and interactive teaching methods, as well as support from the principal and parents. The media also help overcome challenges such as limited attention span and difficulties processing abstract information. In conclusion, colored images are an integral component that modifies and adapts the learning process, effectively improving learning outcomes for students with intellectual disabilities in understanding basic geometry concepts.